Predictive Factors of Dependency in Activities of Daily Living Following Limb Trauma in the Elderly - Safa, Azade (Trauma Mon, 2016)
BACKGROUND: Traumatic injuries in the elderly often lead to permanent disabilities and long-term treatments that can adversely influence their activities of daily of living (ADL). The effect on ADL is an important outcome in elderly trauma. OBJECTIVES: The present study was designed to evaluate the predictive factors of dependency in ADL following limb trauma in elderly referred to Shahid Beheshti Hospital, Kashan, Iran, in 2013. PATIENTS AND METHODS: This descriptive study was conducted on 200 traumatic patients admitted to the trauma emergency ward of Shahid Beheshti hospital in 2013. The questionnaire used in this study had three parts: demographic data, information related to trauma, and an independence scale of ADL (ISADL). The ISADL was completed in the emergency ward to declare pre-traumatic status; it was also completed one and three months after trauma. Statistical analysis was conducted by the t-test and analysis of variance (ANOVA). The repeated measure was used to study the trend of the ISADL and other demographic variables. The multiple regression analysis was also used to declare the predictive variables related to the ISADL. RESULTS: The study population consisted of 81 males (40.5%) and 119 females (59.5%). The participants’ average age was 70.57 ± 9.05 years. In total, 80.5% of the elderly were completely independent in ADL before trauma; this decreased to 13.5% one month after trauma. The repeated measure analysis showed a significant improvement in the ISADL three months after trauma. Gender, age, and education had significant interaction with the ISADL. The multiple regression analysis showed that type of trauma and location of injured organ had predictive values related to the ISADL, one and three months after trauma. The place and cause of trauma, and having surgery showed a significant relationship with the ISADL three months after trauma. CONCLUSIONS: Many factors, such as gender, age, education, type of trauma, and location of injured organ, may predict ADL following limb trauma.